The Leadership Skills Series: Utilizing Videos to Address Leadership Skills - Matthew Sowcik; Jennifer Wert; Jera Niewoehner-Green (EDIS)
This initial publication in the Leaders Skills Series provides Extension professionals with a brief introduction on how to utilize short leadership videos available on the internet to develop specific skills in large or small group settings. The publication also provides an overview of the Leadership Skills Series in Appendix A.